Child Self-Inflicted Chronic Osteomyelitis of the Mandible: A Case Report: Self-Inflicted Osteomyelitis - Esteghamat, Amirfarshad; Kashefi Baher, Mohammadreza; Habibollahi, Mobina; Arefifard, Hamidreza; Mashhadiabbas, Fatemeh (Regeneration, Reconstruction & Restoration (Triple R), 2025)
Osteomyelitis is an inflammatory condition of bone caused by infection, rarely affecting the maxillofacial region in children, often linked to systemic predisposing factors. This study reports a case of an 8-year-old boy presented with exposed mandibular bone following self-extraction of a deciduous tooth. Radiographic evaluations revealed an ill-defined radiolucent lesion in the left mandible. Laboratory tests showed elevated Erythrocyte Sedimentation Rate (ESR) and Positive C-reactive Protein (CRP) levels. Histopathologic examination confirmed osteomyelitis, characterized by nonvital lamellar bone, bacterial colonization, and chronic inflammatory cells infiltration, indicating the diagnosis of chronic osteomyelitis. This case highlights the need to consider osteomyelitis in non-healing extraction sockets, even in patients without systemic disease and within an age group where the condition is uncommon.